2010
DOI: 10.1186/1465-9921-11-98
|View full text |Cite
|
Sign up to set email alerts
|

Health status in COPD cannot be measured by the St George's Respiratory Questionnaire alone: an evaluation of the underlying concepts of this questionnaire

Abstract: BackgroundImproving patients' health status is one of the major goals in COPD treatment. Questionnaires could facilitate the guidance of patient-tailored disease management by exploring which aspects of health status are problematic, and which aspects are not. Health status consists of four main domains (physiological functioning, symptoms, functional impairment, and quality of life), and at least sixteen sub-domains. A prerequisite for patient-tailored treatment is a detailed assessment of all these sub-domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 32 publications
1
22
0
2
Order By: Relevance
“…The CCQ was chosen for this study because it has proven reliability, validity, responsiveness, and high reproducibility 25. In addition, the CCQ is very concise and easily understood by patients,27 while providing information on symptoms and damage that better reflected their HRQoL 28. Permission was obtained prior to this study.…”
Section: Methodsmentioning
confidence: 99%
“…The CCQ was chosen for this study because it has proven reliability, validity, responsiveness, and high reproducibility 25. In addition, the CCQ is very concise and easily understood by patients,27 while providing information on symptoms and damage that better reflected their HRQoL 28. Permission was obtained prior to this study.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies reported that IL-10 production in response to lipopolysaccharide was impaired in monocyte/macrophage lineage of asthmatics compared with normal subjects [29, 30]. On the contrary, other studies reported an increase in IL-10-producing T cells and macrophages in asthmatic airways compared with normal subjects, and that those cells were further increased after allergen challenge [20,31,32,33].…”
Section: Discussionmentioning
confidence: 82%
“…Lung Disease (GOLD (24)(25)(26). Embora não necessariamente causalmente associada com a doença, à existência de DPOC podem realmente aumentar o risco de outra doença.…”
Section: Global Initiative For Chronic Obstructiveunclassified